The land and people of South Africa - Paton, Alan (Philadelphia Lippincott, 1972)
Introduces the land, history, natural resources, industries, government, customs, people, and racial problems of the southernmost country on the African continent.
Includes index.
Keywords: South Africa -- Juvenile literature; South Africa -- Description and travel